Anorexia nervosa versus hyperinsulinism: therapeutic effects of neuropharmacological manipulation - Fuad Lechin; Bertha van der Dijs; Betty Pardey-Maldonado; et al (Dove Medical Press, 2011)
Fuad Lechin1,2, Bertha van der Dijs1,2, Betty Pardey-Maldonado1, Scarlet Baez1, Marcel E Lechin31Sections of Neuroendocrinology, Neuropharmacology, and Neurochemistry, Department of Pathophysiology, Institute of Experimental Medicine, Faculty of Medicine, Universidad Central de Venezuela, Caracas; 2Instituto de Vias Digestivas Caracas, Centro Clínico Profesional Caracas, Venezuela; 3Department of Internal Medicine, Texas A & M Health Science Center, College of Medicine, Texas, USABackground: We have demonstrated that anorexia nervosa is underpinned by overwhelming adrenal sympathetic activity which abolishes the neural sympathetic branch of the peripheral autonomic nervous system. This physiological disorder is responsible for gastrointestinal hypomotility, hyperglycemia, raised systolic blood pressure, raised heart rate, and other neuroendocrine disorders. Therefore, we prescribed neuropharmacological therapy to reverse this central and autonomic nervous system disorder, in order to normalize the clinical and neuroendocrine profile.Methods: The study included 22 female patients with anorexia nervosa (10 restricted type, 12 binge-eating type) who received three months of treatment with amantadine 100 mg/day. We measured blood pressure, heart rate, and circulating neurotransmitters, (noradrenaline, adrenaline, dopamine, platelet serotonin, free plasma serotonin) during supine resting, one minute of orthostasis, and a five-minute exercise test before and after one, two, and three months of treatment with amantadine, a drug which abrogates adrenal sympathetic activity by acting at the C1(Ad) medullary nuclei responsible for this branch of the peripheral sympathetic activity.Results: We found the amantadine abolished symptoms of anorexia nervosa from the first oral dose onwards. Normalization of autonomic and cardiovascular parameters was demonstrated within the early days of therapy. Abrupt and sustained increases in the plasma noradrenaline:adrenaline ratio and disappearance of abnormal plasma glucose elevation were registered throughout the three-month duration of the trial. Significant and sustained increases in body weight were documented in all cases. No relapses were observed.Conclusion: We have confirmed our previously published findings showing that the anorexia nervosa syndrome depends on the hypomotility of the gastrointestinal tract plus hyperglycemia, both of which are triggered by adrenal sympathetic hyperactivity. The above neuroendocrine plus neuroautonomic and clinical disorders which underpinned anorexia nervosa were abruptly suppressed since the first oral dose of amantadine, a drug able to revert the C1(Ad) over A5(NA) pontomedullary predominance responsible for adrenal and neural sympathetic activity, respectively. Keywords: amantadine, anorexia nervosa, adrenal sympathetic activity, hyperglycemia, hyperinsulinism, neural sympathetic activity